2021
DOI: 10.1007/s13300-021-00997-0
|View full text |Cite
|
Sign up to set email alerts
|

Glycemic Control and Prevention of Diabetic Complications in Low- and Middle-Income Countries: An Expert Opinion

Abstract: Introduction Trends on glycemic control and diabetes complications are known for high-income countries, but comprehensive data from low- and middle-income countries (LMIC) are lacking. Methods This is an expert opinion based on two retrospective studies. Here we examine the recent subset analysis of relevant data from the IDMPS Wave 7 (International Diabetes Management-Practices Study, 2015–2016) and the GOAL study conducted in multiple LMICs. Results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 31 publications
2
11
0
Order By: Relevance
“…In a single-centre study, glycated haemoglobin variability was independently associated with the development of nephropathy. 14 , 49 The results of this single-centre study lend further support to this finding reported in Saudi Arabian residents. In addition, high BMI was significantly associated with diabetic nephropathy.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…In a single-centre study, glycated haemoglobin variability was independently associated with the development of nephropathy. 14 , 49 The results of this single-centre study lend further support to this finding reported in Saudi Arabian residents. In addition, high BMI was significantly associated with diabetic nephropathy.…”
Section: Discussionsupporting
confidence: 86%
“…12,13 The incidence of microvascular complications caused by T2D is increasing, primarily in low-and middle-income countries. 14 In Saudi Arabia, the incidence of T2D microvascular complications among people aged 18 years and older is approximately 10%-40%, which increases over time. An increase in the incidence of T2D microvascular complications in Saudi Arabia could be attributed largely to the modifiable behavioural risk factors, such as sedentary lifestyle, excess weight, unhealthy diet, and smoking tobacco products.…”
Section: Introductionmentioning
confidence: 99%
“…So, it must be offered to diabetics to monitor this complication. As per expert opinion,[ 22 ] simple measures like early screening, health education and primary prevention are at modest cost as compared with hospitalization and managing complications. This study also suggests future directions in regard to study in prediabetics, use of neuropathy scale, and interventional studies taking these results as a baseline work.…”
Section: Discussionmentioning
confidence: 99%
“…[ 2 ] The poor glycemic control rate was higher in developing countries comparing with USA and European countries (63.0% vs 47.8% vs 46.4%%). [ 27 ] In underdeveloped country, the diagnosis of T2DM was made when patients present with retinopathy, nephropathy and other complications, resulting in a consequent loss of treatment efficacy. [ 28 ] In our study, most of patients were short duration with less than 10 years while most of them are with complications.…”
Section: Discussionmentioning
confidence: 99%